The evaluation of competence in language classroom: which principal and Which use? - BOUCHEMAA, Saoussen (Journal of Human Sciences, 2022)
What can we evaluate in a language classroom ? Knowledge and competence. Competence evaluation is a process in which we put the process in favour, evaluation serves competence development. It is from this context that the questions of classroom evaluation competence will be discussed in orde to know the best objectives and principals adopted for a superior teaching.the questions asked through this study are : how and according to which criteria the learner will be evaluated according to competence approach?which form an evaluation can take? What is the effect of competence approach on the evaluation? The methodology present in this article give responses and remediations for teachers responding to the criteria demanded.